Correlation between Body Mass Index and Fasting Blood Glucose Level in a Selected Group of Teenagers in Bangladesh - Howlader, Md Hanif; Islam, AKM Mazharul; Rahman, Md Mostafizur; Mili, Umme Sadia; Nur, Rommana Sayla; Kibria, Md Golam (Medicine Today, 2018)
The trend of increasing overweight and obesity is not related to genetic factors only; rather majority of this burden is attributable to the environmental factors. The aim of the study was to observe the correlation between body mass index (BMI) and fasting blood glucose (FBG) level in a selected group of teenagers of Bangladesh. A cross sectional study was conducted involving 39 male and 41 female MBBS students of Faridpur Medical College during 06-04-2014 to 22-05- 2014 by purposive sampling. Data were collected using a questionnaire & check list. Out of 80 students 48.8% male, 51.2% female, 12.5% underweight, 67.5% normal, 16.2% overweight & 3.8% was obese. Mean age of the students was 18.99, BMI 21.99, SBP 121.12, DBP 79.19 and FBG 4.53. Most of students were normotensive (SBP 88.8%; DBP 96.2%) & a few students (SBP 8.8% & DBP 3.8%) were hypertensive. Majority of students (66.2%) were normoglycemic and rest of the students were hypoglycemic. Correlation between BMI and FBG (P=0.65) was not significant but correlation between BMI and systolic blood pressure (SBP) (p<0.0001); BMI & diastolic blood pressure (DBP) (p<0.05) was significant. Comparison of SBP between male and female students showed (p<0.001) was significant. BP and family history of hypertension showed (x2=5.85), p=0.05 level of significance. BMI and FBG showed no significant correlation. BMI and BP showed positive correlation. Male has higher BP than female. Students with family history of hypertension are prone to develop hypertension. Medicine Today 2018 Vol.30(2): 74-77